IMPLEMENTASI MODEL PROBLEM BASED INSTRUCTION (PBI) TERHADAP SIKAP ILMIAH DAN LITERASI SAINS PADA MATA KULIAH ILMU ALAMIAH DASAR - Peby Ziana Sirojul Munir (JIP: Jurnal Ilmu Pendidikan, 2023)
The purpose of this study was to determine: 1) Implementation of learning with a problem based instruction (PBI) model on students' scientific attitudes and scientific literacy. 2) The relationship between scientific attitudes and scientific literacy in learning by applying the problem based instruction (PBI) model. 3) Student response to learning by applying the problem based instruction (PBI) learning model. In the implementation of this research, the method used is the Quasy Experiment method which aims to examine the variables after being given treatment. In practice, the two experimental groups were given different treatments. The two experimental treatment groups were given an initial test (pre test) and a final test (post test) with the same questions and have been tested in different classes from the experimental class. The purpose of pre-test and post-test is to obtain gain data as a result of treatment, namely post-test data minus pre-test data. Based on the results of the study, the authors conclude that: 1) The implementation of learning with the Problem Based Instruction (PBI) model has a relationship with the scientific attitude of students with the acquisition of learning experiences in solving problems such as scientists who are able to change students' attitudes and views towards science. 2) Implementation of learning with a problem based instruction (PBI) model can improve students' scientific literacy this is because the PBI learning process can activate the learning atmosphere to be fun and livelier. 3) There is a significant relationship between the implementation of the problem based instruction (PBI) model with scientific attitudes with scientific literacy in learning which is indicated by the higher the implementation of the problem based instruction (PBI) model, the higher the student's scientific attitude as well as the higher student's scientific literacy ability higher too.